STUDI KASUS DAN PRAKTIK LAPANGAN SUPERVISI & KEPEMIMPINAN PENDIDIKAN ISLAM: IMPLEMENTASI DALAM MENINGKATKAN MUTU PENDIDIKAN - Burhan, Mohammad Nurul; Manshur, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the practice of Islamic education supervision and madrasah principal leadership in the field, and to analyze the supporting factors, inhibiting factors, and their impact on the quality of Islamic education. The method used is qualitative research with a case study type. The research location is at an Islamic educational institution in Bojonegoro Regency. Research subjects include the madrasah principal, teachers, and educational staff. Data collection techniques used observation, interviews, and documentation. The results show that: (1) The practice of Islamic education supervision is carried out through classroom observations, checking learning devices, learning evaluations, discussions, and teacher coaching with a humanistic approach; (2) The madrasah principal's leadership is democratic, communicative, religious, and based on exemplary; (3) Supporting factors include good communication, religious culture, and institutional support; (4) Inhibiting factors include time constraints of supervisors, administrative burden, and lack of teacher understanding; (5) Positive impacts include increased teacher professionalism and learning quality. In conclusion, effective Islamic education supervision and leadership must be implemented humanistically, democratically, and based on Islamic values.